Memorandum of understanding between Universiti Teknologi MARA and Yayasan KRU / Fakulti Filem, Teater dan Animasi - Universiti Teknologi MARA, Fakulti Filem, Teater dan Animasi (Universiti Teknologi MARA (UiTM), 2020)
Memorandum of understanding on friendship and cooperation for friendship, cooperation, promotional of mutual understanding, academic, cultural and personnel exchange.